The Canada-Caribbean Remittance Corridor : Fostering Formal Remittances to Haiti and Jamaica through Effective Regulation - Todoroki, Emiko; Vaccani, Matteo; Noor, Wameek (World Bank, 2012)
The World Bank has been at the global forefront in research on remittances. Studying over twelve bilateral remittance corridors thus far, the financial market integrity unit has focused its research on remittance market integrity issues and the specific incentives influencing the choices of channels to send money home. Initially conducted at the request of Department of Finance, Canada, this corridor, Canada-Caribbean, has clearly distinguished itself from other bilateral remittance corridors studied in the past. At the originating end of this corridor, these distinguishing features include a country that, throughout its history, has made immigration one of its primary social and economic building blocks. This corridor focuses on Jamaica and Haiti, two of the Caribbean's primary labor exporters and also the countries with the two largest Caribbean communities in Canada. Given the importance of remittances in the region, there is a need for effective, yet proportionate regulation. Risk must be effectively mitigated along potentially vulnerable routes, while innovation, competition and transparency in the remittance markets must be encouraged. Regulatory frameworks that reflect local conditions and are proportionate to the risks involved will facilitate the provision of services of the highest quality to migrants and their families. It is hoped that research provided from this study will generate policy dialogues among all relevant stakeholders, and assist national authorities in their efforts to effectively regulate and supervise the remittance markets. National authorities should continue to encourage the use of formal transfers and develop more reliable and competitive remittance channels. These channels must efficiently meet the varied needs of Caribbean migrant workers and their families in the safest and most secure environment possible.